2008
DOI: 10.1007/s12149-008-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m hexamethyl propylene amine oxime-labeled leukocyte scintigraphy at three different times in active ulcerative colitis: comparison with colonoscopy and clinico-biochemical parameters in the assessment of disease extension and severity

Abstract: Tc-99m HMPAO-labeled leukocyte scintigraphy has been found to be correlated well with colonoscopy in the assessment of both the extension and severity of UC. We recommend 2 h scintigraphic imaging because it provides the largest area under the curve value and decreases the number of false-positive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The 99m Tc-HMPAO WBC scintigraphy as an alternative to the invasive gold standard represented by endoscopy with biopsy is a reliable method both for diagnosis and follow-up in pediatric inflammatory bowel disease (IBD) (36,37). Just a few studies about pediatric patients can be found in the literature, and the results of these studies showed sensitivity between 84% and 93%, specificity between 81% and 93% in the diagnosis of IBD (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 99m Tc-HMPAO WBC scintigraphy as an alternative to the invasive gold standard represented by endoscopy with biopsy is a reliable method both for diagnosis and follow-up in pediatric inflammatory bowel disease (IBD) (36,37). Just a few studies about pediatric patients can be found in the literature, and the results of these studies showed sensitivity between 84% and 93%, specificity between 81% and 93% in the diagnosis of IBD (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Just a few studies about pediatric patients can be found in the literature, and the results of these studies showed sensitivity between 84% and 93%, specificity between 81% and 93% in the diagnosis of IBD (38,39). The 99m Tc-HMPAO labeled WBC scintigraphy has proved itself in correctly defining IBD remission and relapses and in defining lesions location, extension, and severity (37). In children with possible IBD the 99m Tc-HMPAO labeled WBC scintigraphy, when compared with endoscopy and biopsy, has a sensitivity rate of 93%, a specificity rate of 97% (38).…”
Section: Discussionmentioning
confidence: 99%
“…The response to an inflammation or acute infection process is characterized by an increase in the local amount of blood, increased vascular permeability in addition to plasma protein exudation, and leukocyte stream [65]. …”
Section: 99mtc-hmpao-labeled Leukocyte Scintigraphy (Tlls)mentioning
confidence: 99%
“…It also demands trained staff, well-equipped laboratories for cell labeling in aseptic conditions not to mention longer performing times. The undeniable advantage of in vitro labeling is, however, given by its distinctly higher image quality due to a selective labeling of granulocytes with lower residual [65]. …”
Section: 99mtc-hmpao-labeled Leukocyte Scintigraphy (Tlls)mentioning
confidence: 99%
See 1 more Smart Citation